E-Learning 2025: Personalizing Children's Learning through AI and Virtual Reality - Hairit, Artamin (LP2M IAI Al-Khairat Pamekasan, 2025)
Digital literacy is an important skill that children must have in facing the challenges of the 21st century. This research aims to identify digital literacy challenges in children and formulate effective educational strategies to support the development of these competencies. The method used is a qualitative study through literature study and thematic analysis of various relevant scientific sources. The results of the study show that children face various challenges in digital literacy, such as limited critical thinking skills, lack of ethics in the use of technology, and exposure to negative content in cyberspace. To overcome this, a collaborative educational strategy is needed between schools, families, and communities. Digital literacy must be integrated into the curriculum, strengthened with a humanist pedagogical approach, and supported by moral values that are consistently instilled. With the synergy of all parties, children can grow up as individuals who are not only technologically capable, but also wise and responsible in facing the digital era.